2017
DOI: 10.20517/2394-5079.2017.28
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of direct-acting antiviral therapy in patients with compensated hepatitis C virus-related cirrhosis

Abstract: Aim:The aim was to assess the clinical impact of direct-acting antiviral treatment in patients with compensated hepatitis C virus-related cirrhosis after one year of follow-up. Methods: An observational retrospective study was conducted on 129 consecutive patients with compensated cirrhosis treated in 2015, analyzing the evolution of liver function and the development of hepatocellular carcinoma and clinical decompensations. Results: The median follow-up time was 16 months. Most patients were males (73%), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…As such, caution should be exercised when comparing safety outcomes reported in clinical trial and real‐world data sets. Results are consistent with previously reported real‐world G/P data, which showed low rates of severe AEs and AEs of special interest 36,37 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As such, caution should be exercised when comparing safety outcomes reported in clinical trial and real‐world data sets. Results are consistent with previously reported real‐world G/P data, which showed low rates of severe AEs and AEs of special interest 36,37 …”
Section: Discussionsupporting
confidence: 92%
“…This is an expected finding, as safety is often under- G/P data, which showed low rates of severe AEs and AEs of special interest. 36,37 In both cohorts, normalization of laboratory parameters was observed across the subgroups. Platelet normalization was rare; however, as low platelet count is a consequence of portal hypertension, platelet count rarely normalizes, even in patients who undergo a liver transplant as the spleen remains large.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…14 We have found that there is a statistically significant improvement in platelet counts and in albumin levels liked Berge study results . 26 Patients who have achieved SVR have shown a significant reduction in the frequency of hepatic encephalopathy episodes, improvement in the management of ascites.…”
Section: Discussionmentioning
confidence: 99%
“…As they cause a rapid decrease in HCV RNA levels leading to a fast decline in natural killer cells (NK) activity. 8 The study aimed to examine new-onset or relapse of HCC in patients receiving Sofosbuvir and Daclatasvir both with and without Ribavirin.…”
Section: Introductionmentioning
confidence: 99%